1986
DOI: 10.2220/biomedres.7.261
|View full text |Cite
|
Sign up to set email alerts
|

<b>FATTY ACID-LINKED PEPTIDES FROM BOVINE P0 PROTEIN IN PERIPHERAL NERVE </b><b>MYELIN </b>

Abstract: P0 glycoprotein in bovine peripheral nerve myelin was solubilized in 0.1% triethylamine and digested with trypsin. The tryptic peptides were separated into 12 peaks by high performance liquid chromatography (HPLC) using a nonionic macroreticular polystyrene resin, Hitachi 3013. In addition to the amino terminal and the carbohydrate-linked peptide, four fatty acid-linked peptides were obtained. The fatty acid-linked peptides contained 0.9 mol fatty acids per molecule. The relative molar ratio of palmitate, stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…Other investigators showed that Cys153, the single acylation site in murine P0 from sciatic nerve, bears a thioester linkage [11]. However, while we found xP0 to be highly stearoylated, P0 from rat and bovine are predominantly palmitoylated [10,11]. Analysis of the fatty acids released by hydrolysis of the murine P0 indicated that the fatty acid composition is ∼50% palmitic, ∼40% stearic, and ∼10% oleic acids [11].…”
Section: Distinct Acylation Profile Of Xp0contrasting
confidence: 57%
See 3 more Smart Citations
“…Other investigators showed that Cys153, the single acylation site in murine P0 from sciatic nerve, bears a thioester linkage [11]. However, while we found xP0 to be highly stearoylated, P0 from rat and bovine are predominantly palmitoylated [10,11]. Analysis of the fatty acids released by hydrolysis of the murine P0 indicated that the fatty acid composition is ∼50% palmitic, ∼40% stearic, and ∼10% oleic acids [11].…”
Section: Distinct Acylation Profile Of Xp0contrasting
confidence: 57%
“…Furthermore, nonglycosylated P0 produced by site-directed mutagenesis at the glycosylation site does not show homophilic adhesion [7]. In addition to glycosylation, the covalently bound long-chain fatty acyl group on Cys153 also appears to be very important for normal P0 homophilic interactions; it has been proposed that acylation promotes association of P0 with the underlying cytoskeleton in a manner similar to that shown for other glycoproteins [9][10][11][12].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Nonenzymatic acylation of a synthetic cysteinecontaining Po peptide with [14C] palmitoyl-CoA To establish whether the integrity of the protein is required for nonenzymatic palmitoylation, a peptide derived from the Po sequence 150-157 (IR-YCWLRR), and comprising the known palmitoylation site (Cys 153), was chemically synthesized and incubated with [ '4 C ] palmitoyl-CoA either alone or in the presence of rat sciatic nerve homogenate. As controls, two other synthetic peptides corresponding to the Po sequences 121-126 (VPTRYG) and 109-115 (KTSQVTL), and containing other potential acylation sites (i.e., Thr "°, Ser"', Thr 114, and Thr 123) (Sakamoto et al, 1986) were also prepared and tested as acyl acceptors in vitro . TLC was used to separate the products of the reaction from the highly labeled and relatively polar palmitoyl-CoA, which remains near the origin of the plate .…”
Section: Labeling Of Proteins At Different Phsmentioning
confidence: 99%